Superconducting properties and fermi-surface topology of the quasi-two-dimensional organic superconductor λ-(BETS)2GaCl4 (BETS ≡ bis(ethylene-dithio)tetraselenafulvalene) - Mielke, C; Singleton, J; Nam, M; Harrison, N; Agosta, C; Fravel, B; Montgomery, L (2001)
The Fermi-surface topology of the organic superconductor λ-(BETS)2GaCl4 has been determined using the Shubnikov-de Haas and magnetic breakdown effects and angle-dependent magnetoresistance oscillations. The former experiments were carried out in pulsed fields of up to 60 T, whereas the latter employed quasistatic fields of up to 30 T. All of these data show that the Fermi-surface topology of λ-(BETS)2GaCl4 is very similar to that of the most heavily studied organic superconductor, κ-(BEDT-TTF)2Cu(NCS)2 (BEDT-TTF ≡ bis(ethylene-dithio)tetrathiafulvalene), except in one important respect: the interplane transfer integral of λ-(BETS)2GaCl4 is a factor ∼5 larger than that of κ-(BEDT-TTF)2Cu(NCS)2. The increased three-dimensionality of λ-(BETS)2GaCl4 is manifested in radio-frequency penetration-depth measurements, which show a clear dimensional crossover in the behaviour of Hc2(T). The radio-frequency measurements have also been used to extract the Labusch parameter determining the fluxoid interactions as a function of temperature, and to map the flux-lattice melting curve.